Effects of drip irrigation regimes on leaf structure, photosynthesis, yield, and quality in Atractylodes chinensis (DC.) Koidz - Lv, Guoshuai; Wu, Yunlong; Li, Zhijun; Zhuang, Defeng; Guo, Yuan; Wang, Zicheng; Gao, Chunxue; Sun, Dezhi; Jia, Junying (Frontiers in Agronomy, 2026)
IntroductionAtractylodes chinensis (DC.) Koidz, a medicinal herb in the Chinese Pharmacopoeia, is grown in sandy soils. However, water scarcity in the Horqin Sandy Land limits its growth, and the effects of irrigation remain poorly studied. This research aimed to determine how irrigation levels affect its yield and quality through leaf structure, physiology, and secondary metabolism.MethodsA field experiment tested five irrigation rates (4500–2500 m3·hm−2). We measured leaf anatomy, photosynthetic parameters, yield, and quality indicators. Results and discussionIrrigation altered leaf anatomy (palisade and spongy tissue thickness). Photosynthetic pigment content showed a initial increase then decrease with reduced irrigation. An irrigation rate of 3500 m3·hm−2 maintained high electron transfer efficiency, carbon assimilation, and key enzyme activity for alkaloid synthesis. While yield declined with less water, quality peaked at moderate irrigation. Moderate irrigation (3500 m3·hm−2) best balances yield and quality by supporting both physiological function and secondary metabolism. These findings offer a theoretical basis and practical guidance for cultivating A. chinensis in water-limited sandy lands under climate change.